The Restoration of Thai Lue the Ethnic Music Culture, (Kub Lue) Samoeng Tai Sub-district, Samoeng District, Chaing Mai Province - จันทะวงศ์, พรสวรรค์ (Community and Social Development Journal, 2019)
This research aimed to study the situation and the ways of restoration of Thai Lue ethnic music culture in Ban Mae Sab, Samoeng District, Chiang Mai Province. Research data was obtained by documents and 100 interviews questionnaires, interviewing 10 key informants, and 3 times focus group. The results were presented as descriptive data following the research objectives. It was found that music culture (Lue singing) is disappearing due to domination of cross-national culture. The rank of three related aspects of this problems were 1) no boarder of digital world in the globalisation, followed by 2) acceptance of consumer culture and 3) wide spread of western culture. Thai Lue ethnic culture restoration committee suggested that there were four aspects of rehabilitation should be undertaken: 1) the adding value of the Thai Lue music culture 2) the preservation of cultural tourism 3) the enhancement of the performance of musicians, singers and actors and 4) the improvement of cooperation of all Lue people.